Adverse effects of fractional laser - Szczepanik-Kułak, Paulina; Krasowska, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2019)
The action of fractional lasers is based on the principle of fractional photothermolysis, which consists in generating in the skin a mesh of microthermal treatment zones surrounded by healthy, undamaged tissue. The most important factors determining the effectiveness of the procedure and the risk of developing adverse effects are: depth, size and density of microthermal treatment zones. The laser beam energy set by the operator is responsible for the depth of microthermal treatment zones penetration into the skin. The amount of intact, healthy tissue remaining between the micro damage zones and their depth depends on the number of laser beam passes. This draws attention to the need for careful selection of treatment parameters, which can only be performed by a person with appropriate qualifications. Fractional laser treatments are an effective form of therapy for many skin diseases and they have a low risk of side effects, most of which are short-term and harmless.